Role of short-range atom-atom forces in formation of the orientational structure of simple molecular crystals - Yakub, E.S. (Физика низких температур, 2019)
An attempt is made to explain the appearance of certain phases having different orientational and spatial structures in the phase diagram of crystals formed by tetrahedral molecules. The classical Monte Carlo method is applied to solid heavy methane CD₄ and the role of various contributions to the non-central intermolecular interactions in formation of the orientational structure in simple molecular crystals is assessed. Зроблено спробу пояснити причину появи деяких фаз, що мають різні орієнтаційні та просторові структури, на фазовій діаграмі кристалів, утворених тетраедричними молекулами. Класичний метод Монте-Карло застосовано до твердого важкого метану CD₄ та оцінено роль різних внесків у нецентральні міжмолекулярні взаємодії в формування орієнтаційної структури простих молекулярних кристалів. Сделана попытка объяснить причину появления некоторых фаз, имеющих разные ориентационные и пространственные структуры, на фазовой диаграмме кристаллов, образованных тетраэдрическими молекулами. Классический метод МонтеКарло применен к твердому тяжелому метану CD₄ и оценена роль различных вкладов в нецентральные межмолекулярные взаимодействия в формирование ориентационной структуры простых молекулярных кристаллов.